Pregnancy-associated diseases are characterized by the composition of the systemic regulatory T cell (Treg) pool with distinct subsets of Tregs - Steinborn-Kröhl, Andrea; Kisielewicz, Anna; Rechenberg, Sophia; Seißler, Nicole; Mahnke, Karsten; Schaier, Matthias; Zeier, Martin; Sohn, Christof (Clinical & experimental immunology, 2012)
Dysregulations concerning the composition and function of regulatory T cells (Tregs) are assumed to be involved in the pathophysiology of complicated pregnancies. We used six-colour flow cytometric analysis to demonstrate that the total CD4+CD127low+/−CD25+forkhead box protein 3 (FoxP3)+ Treg cell pool contains four distinct Treg subsets: DRhigh+CD45RA-, DRlow+CD45RA-, DR-CD45RA- Tregs and naive DR-CD45RA+ Tregs. During the normal course of pregnancy, the most prominent changes in the composition of the total Treg cell pool were observed between the 10th and 20th weeks of gestation, with a clear decrease in the percentage of DRhigh+CD45RA- and DRlow+CD45RA- Tregs and a clear increase in the percentage of naive DR-CD45RA+ Tregs. After that time, the composition of the total Treg cell pool did not change significantly. Its suppressive activity remained stable during normally progressing pregnancy, but decreased significantly at term. Compared to healthy pregnancies the composition of the total Treg cell pool changed in the way that its percentage of naive DR-CD45RA+ Tregs was reduced significantly in the presence of pre-eclampsia and in the presence of preterm labour necessitating preterm delivery (PL). Interestingly, its percentage of DRhigh+CD45RA- and DRlow+CD45RA- Tregs was increased significantly in pregnancies affected by pre-eclampsia, while PL was accompanied by a significantly increased percentage of DR-CD45RA- and DRlow+CD45RA- Tregs. The suppressive activity of the total Treg cell pool was diminished in both patient collectives. Hence, our findings propose that pre-eclampsia and PL are characterized by homeostatic changes in the composition of the total Treg pool with distinct Treg subsets that were accompanied by a significant decrease of its suppressive activity.